Quaternary Stratigraphy and History, Quesnel, British Columbia - Clague, John (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1988)
ABSTRACTThick Quaternary sediments at Quesnel, British Columbia, provide a record of the late Quaternary history of an area near the centre of the former Cordilieran Ice Sheet. These sediments, in part, fill stream valleys that were cut sometime prior to the Late Wisconsinan Fraser Glaciation. Of special note are (1) fluvial or glaciofluvial sand and gravel deposited by aggrading streams, perhaps in part during early Fraser time; (2) thick glaciolacustrine mud, sand, and diamicton laid down later as glaciers advanced across central British Columbia; and (3) glaciolacustrine sediments similar to (2), but deposited in an ice-dammed lake at the end of the Fraser Glaciation. The stratigraphy is punctuated by colluvial deposits that are products of landslides from valley walls at various times during the late Quaternary; this process continues to the present. During the Fraser Glaciation, glaciers from the Coast and Cariboo Mountains coalesced and flowed north over central British Columbia. Fraser Glaciation advance sediments and older Pleistocene deposits were partially removed by this ice sheet and the eroded remnants mantled with till. At the end of this glaciation, the Cordilieran Ice Sheet downwasted and receded southward along an irregular front across the study area. Large amounts of sediment were deposited in glacial lakes dammed by the southward-retreating ice. With complete déglaciation of the interior, glacial lakes drained and the present drainage system was established. At first, valleys were partially aggraded with sand and gravel, but later, streams dissected valley fills to produce a series of terraces at successively lower levels.